Modeling Of Construction Firms Sustainability - Said, Ilias; Rashideh, Waleed Mohamad; Osman, Omar; Abd. Razak, Arman (2009)
Sustainability is a hot debatable issue over the world, constantly being discussed by huge number of professionals’.